2007
DOI: 10.1161/hypertensionaha.106.081679
|View full text |Cite
|
Sign up to set email alerts
|

Renal Albumin Excretion

Abstract: Abstract-Albumin excretion marks early glomerular injury in hypertension. This study investigated heritability of albumin excretion in twin pairs and its genetic determination by adrenergic pathway polymorphism. Genetic associations used single nucleotide polymorphisms at adrenergic pathway loci spanning catecholamine biosynthesis, storage, catabolism, receptor action, and postreceptor signal transduction. We studied 134 single nucleotide polymorphisms at 46 loci for a total of Ͼ51 000 genotypes. Albumin excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…14 Similar results were reported more recently in a slightly larger sample showing that both plasma and urinary E and NE were significantly heritable and ranged from 0.49 to 0.72. 6,13 We are not aware of other heritability studies estimating the basal sympathetic tone by means of overnight urinary excretion rates of both NE and E. In principle, catecholamine levels in blood may more accurately reflect sympathetic activity than overnight urinary excretion rates of NE and E. However, collection of overnight urine for measurement of catecholamine excretion rates has a number of advantages. Catecholamine excretion rates provide an integrated measure of 'steady-state' operating levels of the sympathetic nervous Abbreviations: DZ, dizygotic twins; MZ, monozygotic twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Similar results were reported more recently in a slightly larger sample showing that both plasma and urinary E and NE were significantly heritable and ranged from 0.49 to 0.72. 6,13 We are not aware of other heritability studies estimating the basal sympathetic tone by means of overnight urinary excretion rates of both NE and E. In principle, catecholamine levels in blood may more accurately reflect sympathetic activity than overnight urinary excretion rates of NE and E. However, collection of overnight urine for measurement of catecholamine excretion rates has a number of advantages. Catecholamine excretion rates provide an integrated measure of 'steady-state' operating levels of the sympathetic nervous Abbreviations: DZ, dizygotic twins; MZ, monozygotic twins.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies investigated heritability of NE and E levels or excretion rates and none of these examined to what extent genetic and environmental influences on these catecholamines overlap. 5,6,[12][13][14] In the present study, we have used overnight urinary excretion rates of NE (U NE V) and E (U E V) as measures of basal sympathetic activity. The overnight urine collections were analyzed by radio immune assay (RIA) for NE and E. We aimed to determine the genetic and environmental contributions to U NE V and U E V and their association using bivariate genetic modeling, and examine the associations of U NE V and U E V with office and ambulatory BP in 91 AfricanAmerican and 101 European-American adolescent and young adult twins from the south-eastern USA.…”
Section: Introductionmentioning
confidence: 99%
“…Such intermediate phenotypes may be influenced earlier and more proximately by the genome than are ultimate disease/clinical traits such as hypertension, and therefore may assist in discovery of hypertension-predisposition loci. 2,3 Intermediate traits in physical, physiological/hemodynamic, 4 autonomic/sympathetic, 5-8 metabolic, 9 inflammatory, 9 oxidative, 5 endothelial, 10,11 and renal 12 pathways displayed significant heritability, typically exceeding that reported for blood pressure itself (eg, Figure 1). With the rapid advance of genome technologies, informed systematic phenotyping of sufficiently large numbers of subjects for genetic studies may now be the rate-limiting step in permitting substantive future advances in complex trait genetics.…”
Section: Manifestations Of Heredity: Heritability Twinmentioning
confidence: 96%
“…Thus, one could speculate that plasma norepinephrine levels in ESRD patients are reflective of the degree of sympathetic nerve activity. Rao et al [Rao, et al 2007] and Masuo et al [Masuo, et al 2007] have shown strong associations between β2-adrenoceptor polymorphisms, elevated plasma norepinephrine levels and elevated HOMA-IR (insulin resistance) or future renal injury, suggesting that stimulated sympathetic nerve activity associated with insulin resistance, may independently play a major role in the onset and development of ESRD without obesity or hypertension. However, the precise mechanisms underlying sympathetic activation in CKD and ESRD have not been clarified.…”
Section: Sympathetic Nerve Hyperactivity In Patients With Esrdmentioning
confidence: 99%